1990
DOI: 10.1002/ccd.1810190204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5F and 7/8F catheters for left ventricular and coronary angiography

Abstract: Fifty-two patients were randomized into two groups of 26 to the use of either 5 or 7/8F catheters for their first left heart cardiac catheterization. Clinical characteristics for the two groups were similar. 5F catheters were significantly inferior to 7/8F catheters in terms of torque control (P less than .001), ease of engaging coronary ostia (P less than .001), and quality of angiograms (P less than .05). Nine patients in the 5F group required a change to 7/8F catheters for completion of the procedure. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…In order to reduce these and improve patient comfort, efforts have been made to reduce progressively the size of cardiac catheters. Earlier studies [5][6][7]12] with 4 and 5 Fr catheters found angiographic quality to be reduced and noted technical problems relating to contrast injection and catheter displacement from the coronary ostia during injection. A study of 4 Fr catheters used from the brachial route [13] also found angiographic quality to be inferior with 4 Fr catheters, with the most marked differences noted in opacification of the LAD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to reduce these and improve patient comfort, efforts have been made to reduce progressively the size of cardiac catheters. Earlier studies [5][6][7]12] with 4 and 5 Fr catheters found angiographic quality to be reduced and noted technical problems relating to contrast injection and catheter displacement from the coronary ostia during injection. A study of 4 Fr catheters used from the brachial route [13] also found angiographic quality to be inferior with 4 Fr catheters, with the most marked differences noted in opacification of the LAD.…”
Section: Discussionmentioning
confidence: 96%
“…Local vascular complications remain the most frequent complication of coronary angiography (0.43%-0.6% of cases) [3] and are more common with larger-size femoral punctures [4]. Early work [5][6][7] with smaller diameter catheters was not encouraging. Despite achieving ambulation at a mean of 2.6 hr, the operators criticized catheter handling and the quality of angiographic images obtained [8].…”
Section: Introductionmentioning
confidence: 97%
“…Improved guiding catheter design has resulted in increased internal diameters, which facilitate the passage of interventional devices without increasing their external diameter, therefore, allowing coronary intervention to be performed using smaller diameter French catheters. A number of studies performed during diagnostic coronary angiography have shown no reduction in significant vascular complications with the use of smaller diameter catheters [4–8], often with compromised image quality and handling characteristics [4–6,8]. Previous trials comparing differently‐sized guiding catheters during percutaneous coronary intervention (PCI) have revealed conflicting results with respect to the incidence of vascular complications [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…One randomized trial showed fewer femoral access site complications with 6 Fr compared to 7/8 Fr for PCI procedures [39]. Randomized trials comparing 5 Fr with larger sheaths for coronary angiography have not shown any differences in access site complications [11,40]. Concerns regarding suboptimal coronary opacification and lower procedural success rates with smaller catheter sizes have not been borne out in randomized trials [11,39].…”
Section: Bleeding Complications With Early Invasive Strategymentioning
confidence: 96%
“…However, advances in equipment, including reductions in device and catheter caliber, have allowed for coronary angioplasty procedures to be performed through 4-6 Fr catheters and sheaths [37][38][39][40]. Several retrospective studies have identified associations between sheath size and access site complications [5,7,8], although other studies have not found any association [6,10].…”
Section: Bleeding Complications With Early Invasive Strategymentioning
confidence: 97%